Optimized nonviral gene delivery for primary urinary renal progenitor cells to enhance cell migration. Issue 12 (22nd August 2019) - Liu, Gary W.; Johnson, Soren L.; Jain, Ritika; Peeler, David J.; Shankland, Stuart J.; Pun, Suzie H.
Abstract: Progressive loss of glomerular podocytes during kidney disease leads to irreversible kidney failure, and is exacerbated by the fact that podocytes are terminally differentiated epithelial cells and unable to proliferate. Regeneration of lost podocytes must therefore derive from nonpodocyte sources. Human urine‐derived renal progenitor cells (uRPCs) are attractive podocyte progenitors for cell therapy applications due to their availability from patient urine and ability to migrate to injured glomeruli and differentiate into de novo podocytes after intravenous administration. Because gene delivery has emerged as an important strategy to augment the functionality and survival of cell therapies prior to injection, in this work we optimized nonviral gene delivery conditions (cell density, DNA dose, % FBS, and transfection material composition) to primary uRPCs. Using the cationic polymer‐peptide conjugate VIPER for gene delivery and the Sleeping Beauty transposon/transposase constructs for gene integration, we optimized transfection parameters to achieve efficient transgene expression (up to 55% transfected cells) and stable transgene expression (>65% integration efficiency) lasting up to 10 days. With these methods, we transfected uRPCs to overexpress CXCR4, an important chemokine receptor that mediates uRPC migration to the kidneys after intravenous injection, and demonstrate that CXCR4‐uRPCs exhibit enhanced migration compared to mock‐transfected cells.